A Preliminary Study on the Molecular Identification of Herpes Simplex Virus Type 1 in Iranian Population (Journal of Sciences, Islamic Republic of Iran)
Herpes Simplex Virus Type 1 (HSV-1) is a member of the Herpesviridae family that causes herpetic disease in human. During the last 25-30 years, many investigations have been conducted on pathogenesis and molecular biology of this virus in several countries. In Iran HSV-1 has been isolated from patients and detected using immunological techniques. In this study, we investigated the molecular aspects of two Iranian isolated viruses by PCR-RFLP of HSV-1 DNA Polymerase gene. The result of Southern blot hybridization indicated that the Iranian isolates are HSV type 1. Moreover, the restriction pattern of the Iranian isolates is different from the KOS strain for DpnI enzyme. It is proposed to use this difference as a molecular marker of the Iranian strain.